Answer:
a) ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
b) ![\frac{4}{12}\,,\,\frac{4}{11}\,,\,\frac{4}{10}\,,...](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B12%7D%5C%2C%2C%5C%2C%5Cfrac%7B4%7D%7B11%7D%5C%2C%2C%5C%2C%5Cfrac%7B4%7D%7B10%7D%5C%2C%2C...)
Step-by-step explanation:
Number of balls in the urn = 12
Number of white balls in the urn = 4
So, number of balls which are not white = 12 - 4 = 8
We know that probability = No. of outcomes/Total number of outcomes
Let
denotes the event of getting white ball by A, B and C
a) each ball is replaced after being drawn.
Probability = Number of white balls/Total number of balls
Solution: ![P(A_i)=P(B_i)=P(C_i)=\frac{4}{12}=\frac{1}{3}](https://tex.z-dn.net/?f=P%28A_i%29%3DP%28B_i%29%3DP%28C_i%29%3D%5Cfrac%7B4%7D%7B12%7D%3D%5Cfrac%7B1%7D%7B3%7D)
b)the balls that are withdrawn are not replaced.
Solution:
If A wins: ![P(A_1)=\frac{4}{12}=\frac{1}{3}](https://tex.z-dn.net/?f=P%28A_1%29%3D%5Cfrac%7B4%7D%7B12%7D%3D%5Cfrac%7B1%7D%7B3%7D)
If A lost and B wins: ![P\left ( B_1|A_1^{c} \right )=\frac{4}{11}](https://tex.z-dn.net/?f=P%5Cleft%20%28%20B_1%7CA_1%5E%7Bc%7D%20%5Cright%20%29%3D%5Cfrac%7B4%7D%7B11%7D)
If A and B lost and C wins: ![P\left ( C_1|A_1^{c}\,B_1^{c} \right )=\frac{4}{10}](https://tex.z-dn.net/?f=P%5Cleft%20%28%20C_1%7CA_1%5E%7Bc%7D%5C%2CB_1%5E%7Bc%7D%20%5Cright%20%29%3D%5Cfrac%7B4%7D%7B10%7D)
and so on....
Answer:
m ∠RMK = 51°
Step-by-step explanation:
m ∠JMK = m ∠RMK + m ∠JMR
10x + 19 = 7x - 26 + 6x + 12
10x +19 = 13x -14
19 = 3x -14
33 = 3x
11 = x
m ∠RMK = 7(11) - 26 = 51°
m ∠JMR = 6 (11) + 12 = 78
Answer:
t=6
Step-by-step explanation:
ground height = 0
(are you sure your formula is correct? isn't it - 16t²?)
if h=16t² +64t+192 is true then
16t² +64t+192 = 0
t² + 4t + 12 = 0
t = (-4 ± √(4² - 4*12)) / 2*1 = (-4 ± √-32) / 2 = -2 ± 2√-2
There is no solution of t
if it is h= - 16t² +64t+192
0 =- 16t² + 64t + 192
t² - 4t - 12 = 0
(t + 2) (t -6) = 0
t should be positive
t = 6 sec
Eliminate parentheses using the distributive property.
... -1 -7g +42 +6g = 36
... 41 -g = 36 . . . . collect terms
... 41 -36 = g . . . . add g-36 to both sides
... 5 = g . . . . . .. . . your answer
I don’t have a very detailed explanation, however the answer should be “A 90-degree counterclockwise rotation about the origin followed by a translation 1 unit to the left”.
You can clearly see a 90° angle here, it’s obvious. Also, the polygon switch counterclockwise. so, you can see.
hope I helped ^^